2004
DOI: 10.3136/fstr.10.389
|View full text |Cite
|
Sign up to set email alerts
|

Dough Properties and Baking Quality of Several Domestic Wheat Flours as Compared with Commercial Foreign Wheat Flour

Abstract: The qualities of flours milled from various kinds of wheats (Norin 61, Hokushin, Nebarigoshi and Haruibuki) grown in Japan were studied for application to breadmaking. Protein contents of these wheat flours were in the range of 7.2 -10.0% , Iower than that of a commercial hard-type wheat flour, Cameria (12.4%). Norin 61, Hokushin and Nebarigoshi had higher peak viscosity and breakdown, Iower final viscosities and setback than those of Cameria, while Haruibuki with high amylose content (29.2% ) had lower peak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Hung et al (20) reported that flour quality is also determined by the properties of dough, which is an intermediate stage in the transformation of wheat flour to end products, such as noodles, bread, and cookies. Dough made from soft wheat flour, which has low PC and gluten quality, exhibits low water absorption, is less stable during mixing, and is less extensible than dough made from strong wheat flour (21). Wheat gluten is the main determinant of the end-use quality of wheat because it improved the quality of dough, including characteristics such as water absorption capacity, cohesivity, and visco-elasticity (3).…”
Section: Resultsmentioning
confidence: 99%
“…Hung et al (20) reported that flour quality is also determined by the properties of dough, which is an intermediate stage in the transformation of wheat flour to end products, such as noodles, bread, and cookies. Dough made from soft wheat flour, which has low PC and gluten quality, exhibits low water absorption, is less stable during mixing, and is less extensible than dough made from strong wheat flour (21). Wheat gluten is the main determinant of the end-use quality of wheat because it improved the quality of dough, including characteristics such as water absorption capacity, cohesivity, and visco-elasticity (3).…”
Section: Resultsmentioning
confidence: 99%
“…Properties of doughs made from whole and partial whole waxy wheat flour were obtained using a farinograph (Brabender model SEW, Germany) according to Approved method 54-21 (AACC International, 2000) as previously described by Hung, Maeda, Yoshikawa, and Morita (2004). An optimum amount of water was added to dough during mixing in the farinograph to obtain 500 BU of consistency.…”
Section: Dough Propertiesmentioning
confidence: 99%
“…Properties of doughs made from whole wheat flours were obtained using a farinograph (Brabender model SEW, Düsseldorf, Germany) according to AACC International Approve method 54-21 15 as previously described by Hung et al 17 Fifty grams of whole wheat flour were mixed at 30 • C at 63 rpm and an amount of water was added to obtain a consistency of 500 Brabender units (BU). The optimum amount of water added was the water absorption of whole wheat flours.…”
Section: Dough Propertiesmentioning
confidence: 99%